Cell Wall Proteomics Reveal Phenotypic Adaption of Drug-Resistant Mycobacterium smegmatis to Subinhibitory Rifampicin Exposure - Giddey, Alexander D.; Ganief, Tariq A.; Ganief, Naadir; Koch, Anastasia; Warner, Digby F.; Soares, Nelson C.; Blackburn, Jonathan M. (Frontiers in Medicine, 2021)
Mycobacterium tuberculosis, the causative agent of tuberculosis disease (TB), kills 1.5 million people annually despite the availability of effective drug treatment, and the rising prevalence of drug resistance threatens to worsen this plight significantly. We previously showed sub-lethal exposure to the front-line anti-TB drug, rifampicin, resulted in substantial adaptive remodelling of the proteome of the model organism, Mycobacterium smegmatis, in the drug sensitive mc2155 strain (WT). Here, we investigate whether these responses are conserved in an engineered, isogenic mutant harbouring the clinically relevant S531L rifampicin resistance-conferring mutation (SL) and distinguish responses that are specific to rifampicin’s RpoB-binding activity from those that are dependent on rifampicin’s presence alone. We verified the drug resistance status of this strain and observed no phenotypic indications of rifampicin induced stress upon treatment with the same concentration as used with WT (2.5 µg/mL). Thereafter, we used a cell wall enrichment strategy to focus attention on the cell wall proteome and observed 253 proteins to be dysregulated in SL bacteria as compared with 716 proteins in WT. We observed that decreased abundance of ABC transporters and increased abundance of ribosomal machinery were conserved in the SL strain, while upregulation of transcriptional machinery, and downregulation of numerous two-component systems, were not. We conclude that the drug-resistant M. smegmatis strain displays some of the same proteomic responses observed in WT and suggest that this evidence supports the hypothesis that rifampicin exercises effects beyond RpoB-interaction alone and that mycobacteria recognise rifampicin as a signaling molecule in an RpoB-independent manner at sub-lethal doses. Taken together, our data indicates a mixed RpoB-independent and RpoB-dependent proteomic remodelling in WT mycobacteria, with evidence for RpoB-independent ABC transporter downregulation, but drug activity-based transcriptional upregulation and two-component system downregulation.